Perceived job insecurity and psychological distress: The moderating role of work values - Elias Kodjo Kekesi; Collins Badu Agyemang (International Journal of Management, Economics and Social Sciences (IJMESS), 2014)
The changing nature of work these days has brought about issues of psychological well-being of employees affected by organizational change. The present study investigated the moderating effect of work values on the relationship between perceived job insecurity and psychological distress among 202 junior employees of selected public and private organizations in Ghana. Results showed that there is a positive relationship between perceived job insecurity and psychological distress whereas work values moderate this relationship. This implied that employees who value extrinsic aspects of work were highly distressed when job insecurity is also perceived to be high. Results were discussed with reference to the frameworks of psychological contract and latent deprivation theories as well as reviewed literature. The practical implication of the finding is that in times of organizational change, managers or change agents should manage negative feelings associated with the uncertainty of future continuance of one's job and invest in human resource management practices that increase extrinsic values which could ultimately lead to employee psychological well-being.
Keywords: A13; I19; J65; 330; Job insecurity; psychological distress; extrinsic work values; intrinsic work values; psychological contract theory; latent deprivation theory